Social Listening: Reputation and trust of ‘sustainable apps’ in the food and fashion sector - Carbone, Federica (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Social listening is a well-established research methodology, valued for its analytical capabilities. This study aims to assess the trust that the population places in online shopping experiences. Using a social listening tool over a year-long research period, data on the relationship between environmental sustainability and online shopping were analysed. The findings confirm that these applications are recognised as promoters of environmentally friendly practices.